2021
DOI: 10.3892/etm.2021.9943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the long non‑coding RNA NEAT1/miR‑129‑5p axis in the diagnosis and prognosis for patients with chronic heart failure

Abstract: Chronic heart failure (CHF) is the leading cause of death worldwide. The regulatory interactions of long non-coding RNA (lncRNAs) and microRNAs (miRs) have important roles in multiple diseases. However, the clinical significance of the nuclear-enriched abundant transcript 1 (NEAT1)/miR-129-5p axis in CHF has remained elusive. The present study explored whether the NEAT1/miR-129-5p axis may be a suitable diagnostic and prognostic marker for CHF. The expression of lncRNA NEAT1 and miR-129-5p in the serum of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
2
13
0
1
Order By: Relevance
“…In addition, one of the studies collected blood from two different locations from the same patients (vein and coronary sinus); 24% of studies used TaqMan assay to measure expression levels of miRNAs; 42% and 29% of studies were conducted in China and Europe between 2010 and 2021, respectively ( Table 1 and online supplementary Table Appendix S1 ). 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, one of the studies collected blood from two different locations from the same patients (vein and coronary sinus); 24% of studies used TaqMan assay to measure expression levels of miRNAs; 42% and 29% of studies were conducted in China and Europe between 2010 and 2021, respectively ( Table 1 and online supplementary Table Appendix S1 ). 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Resultsmentioning
confidence: 99%
“…The dysregulated miRNAs (miR-19b, miR-129-5p, miR-221-3p, miR-208a, etc.) may provide non-invasive biomarkers for the diagnosis and prognosis of HF ( 29 , 36 , 62 , 64 ). Therefore, the practicable detection methods are essential to ensure the accuracy and precision of miRNAs ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating lncRNA could act as a prognostic factor for disease. In previous study, NEAT1 was reported as an unfavorable prognostic factor in chronic heart failure patients by log-rank test and ROC analysis [ 39 ]. Further, Chen et al also found that NEAT1 was an unfavorable factor in acute ST-segment elevation myocardial infarction by ROC analysis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%